Charleston Harbor, South Carolina. Spoil Disposal Study. - CORPS OF ENGINEERS CHARLESTON SC CHARLESTON DISTRICT (1966)
Shoaling in Charleston Harbor iss expected to continue resulting in maintenance dredging at the rate of 10,148,000 cubic yards annually if the average annual discharge at the Pinopolis Hydroelectric Power Plant is 15,600 cubic feet per second. Maintenance dredging costs are estimated to average $3,646,700 during the next 60-year period, 1965 to the year 2024. Sufficient prospective disposal sites appear available to accommodate this spoil material but cost will increase as the nearby disposal areas are depleted and the more distant areas are placed into use. Cutterhead pipeline dredges will remain the most efficient means of maintaining projects upstream of Shutes Folly Island and hopper dredges for those downstream from this point. Shoaling rates are related to the fresh-water inflow. A reduction of the average annual discharge at the Pinopolis Hydroelectric Power Plant to 3,000 cfs will result in a decrease in the maintenance dredging rate to 2,968,000 cubic yards annually and in the average cost over a 50-year period (1975-2024) to $1,217,300.